2013
DOI: 10.5194/hessd-10-255-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation in turbidity with precipitation and flow in a regulated river system – River Göta Älv, SW Sweden

Abstract: The turbidity variation in time and space is investigated in the downstream stretch of the river Göta Älv in Sweden. The river is heavily regulated and carries the discharge from the largest fresh water lake in Sweden, lake Vänern, to the outflow point in Göteborg Harbour on the Swedish west coast. The river is an important waterway and serves as fresh-water supply for 700 000 users. Turbidity is utilised as an indicator to ensure sufficient quality of the intake water to the treatment plant. The overal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 42 publications
3
15
0
2
Order By: Relevance
“…The same appeared to occur at subcatchment level, where sediment fluxes were even lower. Several studies have also shown lower unit-area runoff and sediment fluxes on stream channels than hillslopes (Constantz, 1998;Feng and Li, 2008;Goransson et al, 2013;Xu, 2014) due to lower slope gradients which promote high infiltration and sediment deposition (Doble et al, 2012;Eder et al, 2014). Results of cumulative runoff (Table 2) showed great annual runoff microcatchment level, which in some years (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…The same appeared to occur at subcatchment level, where sediment fluxes were even lower. Several studies have also shown lower unit-area runoff and sediment fluxes on stream channels than hillslopes (Constantz, 1998;Feng and Li, 2008;Goransson et al, 2013;Xu, 2014) due to lower slope gradients which promote high infiltration and sediment deposition (Doble et al, 2012;Eder et al, 2014). Results of cumulative runoff (Table 2) showed great annual runoff microcatchment level, which in some years (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…These sediments are, however, redeposited in lower reaches of basins as slope gradients become smoother [ Doble et al ., ; Eder et al ., ]. Other factors explaining low sediment exports at river drainage basin outlets include the time lag of flow behind rainstorms [ Goransson et al ., ] and buffering effect by groundwater [ Zheng et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in this study, lower turbidity does correlate to the higher DO values downstream. Other water quality studies have demonstrated a strong relationship between distance from the discharge point and suspended sediment concentrations, with temporal and spatial variability linked to flow geomorphology .…”
Section: Resultsmentioning
confidence: 96%